High-strength cover plate glass material for space as well as preparation method and application of high-strength cover plate glass material

By adopting specific glass compositions and process treatments, a high-intensity cover glass material suitable for star-sensitive optical system lenses was prepared, which solved the problem of insufficient optical performance in the prior art and achieved a comprehensive performance of wide spectrum, low stray light and high bending intensity.

CN119707280APending Publication Date: 2025-03-28CNBM PHOTONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510010759.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to provide a cover glass material that can meet the demands of star-sensitive optical system lenses for high intensity, wide spectral range, low stray light and high bending intensity, especially in the fields of space detection and intelligent vision.

Method used

A glass composition is adopted, which consists of 50-60% SiO2, 0-3% Bi2O3, 0-5% PbO, 10-18% Na2O, 3-8% K2O, 0-5% B2O3, 10-18% Al2O3, 10-18% ZrO2, 1-6% MgO, 1-6% CaO and 0.1-1% As2O3, cover glass materials with excellent optical properties are prepared by high-temperature melting, mechanical molding, annealing, reduction treatment and chemical strengthening.

Benefits of technology

It has achieved a wide spectral range and excellent spectral transmittance, excellent anti-blocking and anti-crosstalk performance, and has high bending intensity. It is suitable for lenses of star-sensitive optical systems, and has broad application prospects in the fields of space detection and intelligent vision.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707280A_ABST
    Figure CN119707280A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength cover plate glass material for space as well as a preparation method and application of the high-strength cover plate glass material. A glass blank of the high-strength cover plate glass material for the space is prepared from the following components in percentage by mass: 50 to 60 percent of SiO2, 0 to 3 percent of Bi2O3, 0 to 5 percent of PbO, 10 to 18 percent of Na2O, 3 to 8 percent of K2O, 0 to 5 percent of B2O3, 10 to 18 percent of Al2O3, 1 to 5 percent of ZrO2, 1 to 6 percent of MgO, 1 to 6 percent of CaO and 0.1 to 1 percent of As2O3. The cover plate glass material prepared from the glass blank consisting of the components has a wide spectral range, excellent spectral transmittance, excellent stray light elimination and crosstalk prevention performance and relatively high bending strength, can be used for preparing a lens of a star sensor optical system, and has a wide application prospect in the fields of space detection, intelligent vision and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass technology, and specifically to a glass material, in particular a high-strength cover glass material for space use, and a preparation method and application thereof. Background Art

[0002] Any discussion of the prior art throughout the specification should not be considered as an admission that such prior art is widely known or forms part of the common general knowledge in the field.

[0003] A star sensor is a precision attitude measurement device that uses stars as a reference source. It plays a vital role in a variety of platforms such as satellites, missiles, and ships. The key performance of this device depends on its optical system, especially the lens component located at the front end of the optical system. The imaging quality of the lens directly determines the measurement accuracy of the star sensor, making it one of the most critical components of the star sensor.

[0004] In the normal operation of the star sensor, its ability is based on the premise of capturing a sufficient number of stars. Given the weak radiation of starlight, especially in the case of strong background light during the day, the weak starlight is easily drowned out. The sky background light is mainly concentrated in the shortwave band, with a peak wavelength of 450~550 nm, and the spectral energy above 900 nm is extremely low. According to the analysis of the mid-latitude summer atmosphere model and the atmospheric transfer model (visibility of 30 km and altitude angle of 60°), solar radiation is mainly shortwave radiation, and its peak radiation wavelength is about 500 nm.

[0005] In order to meet these specific needs, the cover glass material of the star sensor optical lens must have the following characteristics: large relative aperture to ensure that sufficient light can be captured even under insufficient light conditions, thereby improving the sensitivity and measurement accuracy of the equipment; wide spectral range to be able to work within a wider spectral range to meet the observation needs at different wavelengths; high stray light elimination capability to effectively eliminate or reduce the influence of background light in the range of 450~550 nm, thereby improving the recognition and measurement accuracy of stellar signals; high mechanical strength to ensure the stability and durability of the lens under extreme environmental conditions.

[0006] At present, cover materials that meet the above requirements are mainly used in the military field, and there is a technological gap between the advanced levels at home and abroad, which limits the development of high-performance star sensors.

[0007] The purpose of the present invention is to overcome or improve at least one disadvantage of the prior art, or to provide a useful alternative. Unless the context clearly requires otherwise, throughout the specification and claims, the words "include", "comprises", etc. should be interpreted from an inclusive perspective rather than an exclusive or exhaustive perspective; that is, from the perspective of "including, but not limited to". Summary of the invention

[0008] Therefore, the purpose of the present application is to provide a glass composition, and a high-strength cover glass material for space prepared from the glass composition, a preparation method thereof, and its application in the field of space detection and the field of intelligent vision. The cover glass material provided by the present invention has a wide spectral range and excellent spectral transmittance, excellent stray light elimination and anti-crosstalk performance, and high bending strength, and can be used to prepare the lens of the optical system of the star sensor, and has broad application prospects in the fields of space detection, intelligent vision, etc.

[0009] Specifically, the present invention provides the following technical features, and the combination of one or more of the following technical features constitutes the technical solution of the present invention.

[0010] In a first aspect of the present invention, a glass composition comprises, by mass percentage, 50-60% SiO2, 0-3% Bi2O3, 0-5% PbO, 10-18% Na2O, 3-8% K2O, 0-5% B2O3, 10-18% Al2O3, 1-5% ZrO2, 1-6% MgO, 1-6% CaO and 0.1-1% As2O3.

[0011] In the embodiment of the present invention, SiO2, as a glass former oxide, is the main component forming the glass skeleton network structure, and exists in the glass structure in the form of [SiO4] tetrahedron. The amount of SiO2 not only affects the melting point and viscosity of the glass, but may also affect the redox reaction balance of the glass, the solubility and reactivity of the clarifier and other additives, and thus indirectly affect the formation and thickness of the absorption layer during the reduction treatment. In particular, under a reducing atmosphere, the content of SiO2 may affect the redox reaction in the glass melt, and then affect the formation and distribution of pigments or other absorption substances in the absorption layer, and then affect the properties and thickness of the absorption layer. Therefore, in the present invention, the content of SiO2 is 50-60% by mass. In some embodiments of the present invention, the content of SiO2 can be further selected from the following content range or be any value in the following content range: 50~60%, 50~58.1%, 50~58%, 50~54%, 50~52%, 52~60%, 52~58.1%, 52~58%, 52~54%, 52~52.6%, 52~52.5%, 52~52.3%, 54~60%, 54~58.1%, 54~58%, 58.1~60%, 58~60%, and the like.

[0012] In an embodiment of the present invention, Bi2O3 is an important additive, and the bismuth element in the glass can be reduced to low-valent bismuth or even metallic bismuth under a high-temperature reducing atmosphere. This reduction process will cause a change in the color of the glass material, which may cause the glass to present a specific color, such as black or gray. The dispersion of bismuth elements in the glass matrix can significantly increase the light absorption capacity of the material and enhance the material's absorption of light. The present invention adjusts the light absorption characteristics of the entire glass by controlling the reduction process to produce Bi particles. In traditional optoelectronic glass materials, to achieve high light absorption efficiency, an absorption layer is usually obtained by coating, which increases the weight and cost of the material and has a negative impact on the efficiency of light transmission. The present invention can form an efficient light absorption area in a thinner glass layer by adding Bi2O3 and reducing it under specific conditions, thereby improving the overall light absorption efficiency without significantly increasing the thickness of the material. In the present invention, the content of Bi2O3 is 0~3% by mass. In some embodiments of the present invention, the content of Bi2O3 can be further selected from the following content range or be any value in the following content range: 0, 0~3%, 0~2.5%, 0~2%, 0~1.5%, 0~1%, 0~0.5%, 0.5~3%, 0.5~1.5%, 0.5~1%, 1~3%, 1~1.5%, 1.5~3%, 1.6~3%, 1.8~3%, 2.0~3%, 2.2~3%, 2.5~3%, 2.8~3%, and the like.

[0013] In the embodiment of the present invention, PbO is an important additive. As a network-external oxide, it not only increases the thermal expansion coefficient and refractive index of the glass, but also reduces the melting temperature, so that the glass has better optical properties by taking away oxygen ions in the Si-O network and causing Si-O network disconnection to form non-bridging oxygen. In the present invention, the content of PbO is 0-5% by mass. In some embodiments of the present invention, the content of PbO can be further selected from the following content range or any value in the following content range: 0, 0~5%, 0~3%, 0~1.5%, 0~1%, 0~0.5%, 0.1~5%, 0.1~3%, 0.1~1.5%, 0.1~1%, 0.1~0.5%, 0.5~5%, 0.5~3%, 0.5~1.5%, 0.5~1%, 0.6~1%, 0.7~1%, 0.8~1%, 0.9~1%, 1~5%, 1~3%, 1~1.4%, 1~1.3%, 1~1.2%, 1~1.1%, 1~1.5%, 1.5~5%, 1.5~3%, 3~5%, and the like.

[0014] In some embodiments of the present invention, the contents of PbO and Bi2O3 are not both 0. The addition of Bi2O3 can make up for the deficiencies of PbO in chemical stability and thermal stability. In some embodiments of the present invention, the sum of the contents of PbO and Bi2O3 is 0.5-6%, preferably 0.5-4%, and more preferably 3.6-4%.

[0015] In the embodiment of the present invention, Na2O and K2O are the oxides of the glass network. The alkali metal ions are easy to move and diffuse in the glass body. At the same time, they can reduce the viscosity of the glass during high-temperature melting, making the glass easy to melt, and are good fluxing agents. + Chemical strengthening is also called ion exchange strengthening. At a certain temperature, the glass is placed in a molten salt (such as molten potassium nitrate) to make the small radius ions (such as Na + ) and large radius ions in molten salts (such as K +) are replaced, thereby generating a "squeezing" effect on the glass surface, forming a surface compressive stress layer, and significantly improving the bending strength and impact resistance of the glass material. This surface compressive stress resists the tensile stress caused by external pressure, effectively reduces the crack propagation starting from the surface of the material, and thus significantly enhances the durability and safety of the material. In the present invention, the content of Na2O is 10-18% and the content of K2O is 3-8% by mass. In some embodiments of the present invention, the content of Na2O can be further selected from the following content range or any value in the following content range: 10~18%, 10~16%, 10~15.1%, 10~13.1%, 10~12.9%, 10~12%, 10~11.9%, 10~11.5%, 10~11%, 10~10.5%, 12~18%, 12~16%, 12~15.1%, 12~13.1%, 12~12.9%, 12.9~18%, 12.9~16%, 12.9~15.1%, 12.9~13.1%, 13.1~18%, 13.1~16%, 13.1~15.1%, 15.1~18%, 15.1~16%, 16~18%, and the like. In some embodiments of the present invention, the content of K2O can be further selected from the following content ranges or any value in the following content ranges: 3-8%, 3-6%, 3-5%, 3-4%, 4-8%, 4-6%, 4.1-6%, 4.5-6%, 4.8-6%, 4-5%, 5-8%, 5-6%, 5.1-6%, 5.5-6%, 5.8-6%, 6-7.9%, 6-7.8%, 6-7.5%, 6-7.3%, 6-8%, and the like.

[0016] In an embodiment of the present invention, B2O3 is a glass former oxide, and B can partially replace Si in silicate glass to form a network structure. In addition, B2O3 has a fluxing effect in glass, which can reduce the high-temperature viscosity of the glass, save costs, and facilitate production. However, as the content of B2O3 increases, the devitrification range of the glass increases, and B2O3 is volatile and can cause pollution to the environment, so the amount should be strictly controlled during the production process. In the present invention, the content of B2O3 is 0-5% by mass. In some embodiments of the present invention, the content of B2O3 can be further selected from the following content ranges or be any value in the following content ranges: 0, 0~5%, 0~3%, 0~2.5%, 0~2%, 1~5%, 1~4%, 1~3%, 2~5%, 2.1~3%, 2.2~3%, 2.8~3%, 2~3%, 2~2.5%, 2.5~5%, 2.5~3%, 3~5%, 3~4.9%, 3~408%, 3~4.5%, 3~4.1%, 3~4%, 3~3.9%, 3~3.8%, 3~3.6%, 3~3.4%, and the like.

[0017] In the embodiment of the present invention, Al2O3 is a glass intermediate oxide, and its content affects the thermal expansion coefficient and chemical and thermal stability of the glass. Al2O3 can increase the mechanical processing performance of the glass, but too much will reduce the material properties. In addition, the volume of [AlO4] in the glass is 41 cm 3 / mol, the volume of [SiO4] is 27cm 3 / mol, [AlO4] is 52% larger in volume than [SiO4], so [AlO4] will increase the voids in the glass, which is beneficial to improving the ion exchange efficiency and making the glass material have excellent chemical strengthening properties. In the present invention, the content of Al2O3 is 10-18% by mass. In some embodiments of the present invention, the content of Al2O3 can be further selected from the following content ranges or be any value in the following content ranges: 10~18%, 10~15%, 10~13%, 10~12%, 10~11.9%, 11.7~12%, 11.6~12%, 11.5~12%, 11.3~12%, 11.8~12%, 11.9~18%, 11.9~15%, 11.9~13%, 11.9~12%, 12~18%, 12~15%, 12~13%, 12~12.9%, 12~12.6%, 12~12.4%, 12~12.3%, 13~18%, 13~15%, 15~18%, and the like. In the present invention, "materiality" refers to a physical property of glass in a high-temperature molten state, which is distinguished by "long / short" and must be accurately detected with the aid of instruments. For example, a rheometer can be used to test the viscosity of a sample in a viscoelastic state and calculate the rate of change of its viscosity. If the rate of change of the glass viscosity is faster, the materiality becomes shorter, and if the rate of change of the glass viscosity is slower, the materiality becomes longer.

[0018] In an embodiment of the present invention, ZrO2 is a glass intermediate oxide, which has the effect of improving chemical stability and preventing alkali metal and alkaline earth metal ions from being exposed. It is also an important component for improving the tensile elastic modulus, and is very helpful for improving the hardness of glass after chemical strengthening. In the present invention, the content of ZrO2 is 1-5% by mass percentage. In some embodiments of the present invention, the content of ZrO2 can be further selected from the following content ranges or any value in the following content ranges: 1-5%, 1-3%, 1-2%, 2-5%, 2.1-5%, 2.6-5%, 2-3%, 3-5%, 3.1-5%, 3.3-5%, 3.6-5%, 3.8-5%, 4-5%, 4.1-5%, 4.6-5%, 4.8-5%, and the like.

[0019] In an embodiment of the present invention, MgO and CaO are alkaline earth metal oxides, and the addition of alkaline earth metal oxides can greatly reduce the phase separation tendency of the glass. At the same time, MgO is added to the alkali-aluminosilicate glass, which has a network breaking and fluxing effect on the glass, and does not cause a substantial disconnection of the network, and can promote the formation of multi-rings in the network structure, including ternary rings, quaternary rings, pentacyclic rings and hexacyclic rings, etc., which not only meets the integrity of the glass connection, but also helps to create gaps between glass structural units, creates exchange channels for ion exchange, and is conducive to the increase of the depth of the compressive stress layer (DOL) after chemical strengthening, thereby affecting the bending strength and overall impact resistance of the glass. In the present invention, the content of MgO is 1-6% by mass, and the content of CaO is 1-6%. In some embodiments of the present invention, the content of MgO may be further selected from the following content ranges or any value in the following content ranges: 1-6%, 1-4%, 1-3%, 1-2%, 2-6%, 2-4%, 2-3%, 3-6%, 3-4%, 4-6%, 5-6%, 5.1-6%, 5.4-6%, 5.6-6%, 5.8-6%, etc. In some embodiments of the present invention, the content of CaO may be further selected from the following content ranges or any value in the following content ranges: 1-6%, 1-4%, 1-3.3%, 1-3%, 1-2%, 1-1.5%, 1-1.3%, 3-6%, 3-3.3%, 3.3%-6%, etc.

[0020] In an embodiment of the present invention, As2O3 can produce the following reaction at high temperature:

[0021]

[0022] O2 is released at high temperature, so that the gas partial pressure of bubbles in the glass liquid is reduced, the volume is increased, and the bubbles rise faster, achieving a good clarification effect. At the same time, the use of As2O3 in the present invention can affect the reducibility of the glass melt, thereby affecting the concentration and distribution of elements in the absorption layer formed after the reduction treatment, and then affecting the properties and thickness of the absorption layer. In the present invention, the content of As2O3 is 0.1~1% by mass. In some embodiments of the present invention, the content of As2O3 can be further selected from the following content range or any value in the following content range: 0.1~1%, 0.1~0.5%, 0.1~0.4%, 0.1~0.2%, 0.2~1%, 0.2~0.5%, 0.2~0.4%, 0.4~1%, 0.4~0.5%, 0.5~1%, 0.51~1%, 0.56~1%, 0.58~1%, 0.6~1%, 0.7~1%, 0.8~1%, 0.9~1%, and the like.

[0023] The various specific technical features described in the above embodiments of the present invention can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations.

[0024] Unless otherwise specified, the numerical range described in the present invention includes all the numerical values ​​within this range, and includes the range value composed of any two numerical values ​​within this range. For example, 0.1~2%, this numerical range includes all the numerical values ​​between 0.1~2%, and includes the range value (0.11~0.19%) composed of any two numerical values ​​within this range (for example: 0.11%, 0.19%); different numerical values ​​of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.

[0025] For example, in some embodiments of the present invention, the glass composition of the present invention comprises, by mass percentage, 50-60% SiO2, 0-3% Bi2O3, 0-5% PbO, 10-16% Na2O, 3-8% K2O, 0.1-5% B2O3, 10-18% Al2O3, 1-5% ZrO2, 1-6% MgO, 1-6% CaO and 0.1-1% As2O3.

[0026] For example, in some embodiments of the present invention, the glass composition of the present invention comprises, by mass percentage, 50-60% SiO2, 0-3% Bi2O3, 0-2.9% PbO, 10-16% Na2O, 3-8% K2O, 0-3% B2O3, 10-17.9% Al2O3, 1-5% ZrO2, 1.1-6% MgO, 1-6% CaO and 0.2-1% As2O3.

[0027] For example, in some embodiments of the present invention, the glass composition of the present invention comprises, by mass percentage, 52~60% SiO2, 0~3% Bi2O3, 0~1% PbO, 10~15.9% Na2O, 5~7.9% K2O, 2.1~3% B2O3, 10~15% Al2O3, 2.1~5% ZrO2, 2~6% MgO, 1~6% CaO and 0.2~1% As2O3.

[0028] For example, in some embodiments of the present invention, the glass composition of the present invention comprises, by mass percentage, 52~60% SiO2, 0~3% Bi2O3, 0.5~3% PbO, 10~15.9% Na2O, 5~7% K2O, 2.1~3% B2O3, 10~12.9% Al2O3, 2.1~5% ZrO2, 2~6% MgO, 1~6% CaO and 0.4~1% As2O3.

[0029] For example, in some embodiments of the present invention, the glass composition of the present invention comprises, by mass percentage, 52~58% SiO2, 1.6~3% Bi2O3, 0.5~1.4% PbO, 10~11.9% Na2O, 5.1~6% or 6~7.9% K2O, 2.1~3% or 3~4.9% B2O3, 12~12.9% Al2O3, 3.1~5% ZrO2, 5.1~6% MgO, 1~3.2% CaO and 0.6~1% As2O3.

[0030] In a second aspect of the present invention, a cover glass blank is provided, which is made of the glass composition described in the first aspect.

[0031] In some embodiments of the present invention, the preparation method of the cover glass blank comprises: mixing the raw materials, melting at a high temperature of 1540-1600°C, stirring, clarifying, then cooling to 1350-1450°C for molding, and annealing at 450-580°C after molding.

[0032] In some embodiments of the present invention, the raw materials may also be selected from the following materials as needed: quartz sand, bismuth oxide (or bismuth nitrate pentahydrate), red lead (or yellow lead), sodium carbonate (or sodium nitrate), potassium carbonate (or potassium nitrate), boric oxide (or boric acid), aluminum hydroxide (or aluminum oxide), zirconium oxide, calcium oxide (or calcium carbonate), magnesium oxide (or basic magnesium carbonate) and white arsenic.

[0033] In a third aspect of the present invention, a light-transmitting glass substrate is provided, which is prepared by mechanically treating the cover glass blank described in the second aspect.

[0034] In an embodiment of the present invention, the mechanical processing includes changing at least one of the physical form, surface quality and appearance of the glass blank. The physical form may be, for example, cutting the glass blank into a desired shape and size, or drilling a desired hole diameter and hole position on the glass blank. The surface quality may be, for example, polishing (e.g., mechanical polishing) to improve the smoothness and transparency of the glass blank surface, or grinding the glass edge to remove the sharp edge and improve safety. The appearance may be, for example, engraving (e.g., mechanical engraving) to make various patterns or logos on the surface of the glass blank.

[0035] In some embodiments of the present invention, the light-transmitting glass substrate is in the shape of a truncated cone, the truncated cone having two parallel upper and lower circular bottom surfaces, and the height of the truncated cone is the vertical distance between the upper and lower bottom surfaces. In an embodiment of the present invention, the light-transmitting glass substrate has a spectral transmittance of 500nm light of ≥90.00%, preferably ≥90.5%, for example, the transmittance can be 90-91.28% or 90.5-91.28%, etc.

[0036] In the fourth aspect of the present invention, a cover glass material is provided, which comprises the light-transmitting glass substrate described in the third aspect above, and a light-absorbing layer arranged on the surface of the light-transmitting glass substrate. In some embodiments of the present invention, the spectral transmittance of the light-transmitting glass substrate to 500nm light is ≥90.00%, preferably ≥90.5%, for example, the transmittance can be 90-91.28% or 90.5-91.28%, etc.; the spectral transmittance of the light-absorbing layer to 500nm light is ≤0.40%, preferably ≤0.30%, for example, the transmittance can be 0.22-0.4%, 0.22-0.36% or 0.22-0.30%, etc.

[0037] In some embodiments of the present invention, the light absorbing layer is produced on the surface of the light-transmitting glass substrate by performing a reduction treatment on the light-transmitting glass substrate.

[0038] In some embodiments of the present invention, the thickness of the absorption layer is ≥501 μm, preferably ≥510 μm, for example, the thickness may be 501-525 μm, 510-525 μm, 517-525 μm or 523-525 μm.

[0039] In some embodiments of the present invention, the reduction treatment is performed under a reducing atmosphere, the reduction treatment time is 3000-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 500-650°C.

[0040] The reduction process usually produces two effects on the glass surface, which in turn form a coloring effect: first, the mutable valence ions in the glass are reduced at high temperatures to produce a change in chemical valence; second, the high temperature hydrogen creates structural defects in the glass, and the defect centers form coloring centers. The reduction reaction forms a light absorption layer in situ on the glass substrate, which is the key to achieving a high stray light elimination function.

[0041] In some embodiments of the present invention, the cover glass material is chemically strengthened glass, and the bending strength of the cover glass material after chemical strengthening is ≥200 MPa, preferably ≥205 MPa, and more preferably ≥210 MPa, for example, the bending strength can be 200-217 MPa, 206-217 MPa, 209-217 MPa or 215-217 MPa. The temperature of the chemical strengthening is 380-480 °C, the time is 30-600 min, and the molten salt used for chemical strengthening is selected from one or more of lithium salts, sodium salts and potassium salts.

[0042] In a fifth aspect of the present invention, a method for preparing the cover glass material described in the third aspect is provided, comprising: obtaining a cover glass blank; Mechanically processing the cover glass blank to obtain a light-transmitting glass substrate; Performing a reduction treatment on the light-transmitting glass substrate so that the surface of the light-transmitting glass substrate forms a light-absorbing layer; Performing secondary machining on the light-transmitting glass substrate after reduction treatment to remove part of the light-absorbing layer so as to expose the light-transmitting area; The glass after the secondary mechanical treatment is chemically strengthened to obtain a chemically strengthened cover glass material.

[0043] In some embodiments of the present invention, the glass composition described in the first aspect is used to prepare a cover glass blank. The preparation method of the cover glass blank comprises: mixing the raw materials, melting at a high temperature of 1540-1600°C, stirring, clarifying, then cooling to 1350-1450°C for molding, and annealing at 450-580°C after molding to obtain the cover glass blank. The mechanical processing and secondary mechanical processing are as described in the third aspect.

[0044] In one embodiment of the present invention, the light-transmitting glass substrate after reduction treatment is subjected to secondary mechanical treatment to remove part of the light-absorbing layer to expose the light-transmitting area. For example, the light-transmitting glass substrate is truncated, and the light-absorbing layers on the upper and lower circular surfaces of the truncated cone are removed by grinding, polishing, etc. (the light-absorbing layers on the sides of the truncated cone are retained). During the treatment process, the parallelism of the upper and lower circular surfaces is ensured to be ≤0.01 mm, the coaxiality is ≤0.02 mm, and the surface roughness is ≤10 nm. The schematic diagram of the truncated cone-shaped glass cover material obtained in this way can be shown as follows:Figure 2 shown.

[0045] In some embodiments of the present invention, the reduction treatment is performed under a reducing atmosphere (such as hydrogen), the reduction treatment time is 3000-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 500-650 °C.

[0046] In some embodiments of the present invention, the temperature of the chemical strengthening is 380-480° C., and the time is 30-600 min.

[0047] In some embodiments of the present invention, the chemical strengthening refers to placing the glass in a salt bath for single or multiple chemical ion exchange, and the salt bath used for ion exchange can be lithium salt, sodium salt, potassium salt or a mixed molten salt of the three. For example, in some embodiments, the molten salt is molten potassium nitrate.

[0048] The method provided by the present invention has process stability, and the glass material prepared by the process method can show stable characteristics, and will not cause non-negligible fluctuations in glass performance due to the adjustment of process parameters within the range (such as temperature, time, pressure, etc. within the range). Of course, it is understandable that within the process range, some higher temperatures can shorten the preparation process compared to lower temperatures. If it is necessary to shorten the time cost as much as possible, those skilled in the art can select a relatively higher temperature within the temperature range disclosed in the present invention during operation.

[0049] In a sixth aspect of the present invention, a lens is provided, comprising the cover glass material described in the fourth aspect or the cover glass material manufactured by the method described in the fifth aspect.

[0050] In the sixth aspect of the present invention, there is provided an application of the glass composition described in the first aspect, the glass cover material described in the fourth aspect, or the lens described in the sixth aspect in the field of intelligent technology applications.

[0051] In some embodiments of the present invention, the application fields of the intelligent technology include the field of space detection and the field of intelligent vision.

[0052] In particular, the glass cover material of the present invention can be used to prepare lenses of star sensor optical systems, such as protective windows of lenses, optical filters or front covers of lenses.

[0053] Through one or more of the above technical means, the following beneficial effects can be achieved: The present invention provides a high-strength cover glass material for space use, which has a wide spectral range and excellent spectral transmittance, the minimum spectral transmittance in the light-transmitting effective area is ≥90.00% (@500 nm~1500 nm), has excellent stray light elimination and crosstalk prevention performance, the transmittance of the light absorption layer is ≤0.40%@500 nm, has high bending strength, and the bending strength is ≥200 MPa. The material can be used to prepare lenses for star sensor optical systems and has broad application prospects in the fields of space detection, intelligent vision, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The drawings constituting part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. The implementation scheme of the present application is described in detail below in conjunction with the drawings, wherein: Figure 1 The figure shows the transmittance comparison of the glass material of Example 3 of the present invention before and after the reduction treatment.

[0055] Figure 2 A schematic diagram of a truncated cone-shaped high-strength cover glass is shown, wherein the side surface of the truncated cone has a black absorption layer.

[0056] Figure 3 A comparison chart of the bending strength values ​​of the glass of Examples 1 to 6 of the present invention and Comparative Examples 1 to 7 after chemical strengthening is shown.

[0057] Figure 4 A comparison chart of the transmittance values ​​of the glass light-transmitting effective area of ​​Examples 1 to 6 of the present invention and Comparative Examples 1 to 7 is shown (thickness 2 mm@500 nm).

[0058] Figure 5 A comparison chart of the transmittance values ​​of the glass absorption layer of Examples 1 to 6 of the present invention and Comparative Examples 1 to 7 (@500nm) is shown. DETAILED DESCRIPTION

[0059] The present application is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0060] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in this application can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in this application are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the content described herein can be applied to the method of this application. The preferred implementation methods and materials described in the text are for demonstration purposes only.

[0061] The invention provides a high-strength cover glass material for space, which comprises, by mass percentage, 50-60% of SiO2, 0-3% of Bi2O3, 0-5% of PbO, 10-18% of Na2O, 3-8% of K2O, 0-5% of B2O3, 10-18% of Al2O3, 1-5% of ZrO2, 1-6% of MgO, 1-6% of CaO and 0.1-1% of As2O3.

[0062] In a further technical solution, the high-strength cover glass material for space use, by mass percentage, comprises: 50-60% SiO2, 0-3% Bi2O3, 0.1-5% PbO, 10-18% Na2O, 3-8% K2O, 0-5% B2O3, 10-18% Al2O3, 1-5% ZrO2, 3-6% MgO, 1-6% CaO and 0.1-1% As2O3. The glass material of the present invention has a wide spectral range and excellent spectral transmittance, has excellent stray light elimination and crosstalk prevention performance after high-temperature reduction treatment, has high bending strength after chemical strengthening, can be used to prepare the lens of the optical system of the star sensor, and has broad application prospects in the fields of space detection, intelligent vision, etc.

[0063] In particular, when the glass material described in the present invention is composed of the above-mentioned components, in some embodiments of the present invention, the glass material of the present invention has a minimum spectral transmittance in the light-transmitting effective area of ​​≥90.00% (@500 nm~1500 nm), a transmittance of the light absorption layer after chemical reduction treatment of ≤0.40%@500 nm, and has the property of being chemically strengthened. After chemical strengthening, the glass has a higher bending strength, and the bending strength is ≥200 MPa.

[0064] Furthermore, the present invention provides a method for preparing a high-strength cover glass material for space use, comprising: after various glass raw materials are uniformly mixed in proportion, the batch material is melted at a high temperature of 1540-1600°C, mechanically stirred, and clarified by auxiliary bubbling, and then cooled to 1350-1450°C and molded by mechanical or manual casting, and annealed at 450-580°C after molding to obtain the glass blank.

[0065] The glass blank is processed into a light-transmitting glass substrate by mechanical processing, such as processing into a truncated cone of a certain size. The truncated cone-shaped light-transmitting glass substrate is subjected to reduction treatment to form a light absorption layer on the surface of the glass substrate. The reduction treatment is carried out under hydrogen, the reduction treatment time is 3000-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 500-650°C.

[0066] The light absorption layer (black) formed on the upper and lower circular surfaces of the truncated cone-shaped transparent glass substrate is removed, and the light absorption layer (black) on the side of the truncated cone is retained.

[0067] The treated truncated cone glass is chemically strengthened to obtain the high-strength cover glass material for space. The temperature of the chemical strengthening is 380-480°C and the time is 30-600 min. The molten salt used for chemical strengthening is selected from one or more of lithium salts, sodium salts and potassium salts. Unless otherwise specified, the molten salt used in the following embodiments is molten potassium nitrate.

[0068] The method provided by the present invention has process stability, and the glass material prepared by the process method can show stable characteristics, and will not cause non-negligible fluctuations in glass performance due to the adjustment of process parameters within the range (such as temperature, time, pressure, etc. within the range). Of course, it is understandable that within the process range, some higher temperatures can shorten the preparation process compared to lower temperatures. If it is necessary to shorten the time cost as much as possible, those skilled in the art can select a relatively higher temperature within the temperature range disclosed in the present invention during operation.

[0069] Testing methods for glass properties in the embodiments of the present invention and comparative examples: The transmittance of the glass sample was measured using a Shimadzu UV-Vis spectrophotometer (UV-3600Plus). The test wavelength range was 300 nm to 1500 nm. The surface of the tested glass sample was optically polished and the sample thickness was 2 mm. (GB / T7962.12-2010).

[0070] The bending strength of the glass sample is measured using a three-point bending tester. The sample size is 3 mm × 4 mm × 40 mm. The four long sides of the tested glass sample are optically polished, the long edges are chamfered, and the end surface of the test sample does not require special treatment. (GB / T 6569-2006) The thickness of the light absorption layer of the glass material after reduction is measured under an optical microscope.

[0071] In the following embodiments and comparative examples of the present invention, unless otherwise specified, the reducing atmosphere is hydrogen, and the molten salt used for chemical strengthening is molten potassium nitrate. The mechanical processing is to grind and polish the upper and lower circular surfaces of the truncated cone with the absorption layer formed on the surface to remove the light absorption layers of the upper and lower circular surfaces, expose the light-transmitting effective area of ​​the glass, and retain the light absorption layer on the side of the truncated cone.

[0072] Example 1 The high-strength cover glass blank for space use in this embodiment is composed of the following components in percentage by mass: 54% SiO2, 0.5% Bi2O3, 3% PbO, 18% Na2O, 3% K2O, 13% Al2O3, 2% ZrO2, 5% MgO, 1% CaO, and 0.5% As2O3.

[0073] Quartz sand, bismuth oxide, red lead, sodium nitrate, potassium carbonate, aluminum hydroxide, zirconium oxide, calcium carbonate, basic magnesium carbonate and white arsenic are used as raw materials. After each glass raw material is mixed in proportion, the batch material is melted at a high temperature of 1540°C, clarified by auxiliary stirring, mechanically formed at 1350°C, and annealed at 450°C to obtain a glass blank.

[0074] The glass blank of this embodiment is processed into a truncated cone of a certain size by precision machining; the truncated cone is subjected to a reduction process at 5000 min, 0.1 MPa, and 520°C to form a light absorption layer on the glass surface. Then, the upper and lower surfaces of the truncated cone with the light absorption layer formed on the surface are machined. The processed glass is chemically strengthened at 400°C for 120 min to obtain the high-strength cover glass material for space use of this embodiment.

[0075] According to tests, the spectral transmittance of the light-transmitting effective area of ​​the high-strength cover glass material for space use in this embodiment is 90.00%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 0.36%@500 nm, and the bending strength of the glass after chemical strengthening is 205.6 MPa.

[0076] Example 2 The high-strength cover glass blank for space use in this embodiment is composed of the following components in percentage by mass: 50% SiO2, 1% Bi2O3, 5% PbO, 12.9% Na2O, 8% K2O, 2% B2O3, 18% Al2O3, 1% ZrO2, 1% MgO, 1% CaO, and 0.1% As2O3.

[0077] Quartz sand, bismuth nitrate red lead pentahydrate, sodium carbonate, potassium carbonate, boric oxide, aluminum hydroxide, zirconium oxide, calcium oxide, magnesium oxide and white arsenic are used as raw materials. The various glass raw materials are mixed in proportion, the batch material is melted at a high temperature of 1558°C, clarified by auxiliary stirring, mechanically formed at 1367°C, and annealed at 476°C to obtain a glass blank.

[0078] The glass blank of this embodiment is processed into a truncated cone of a certain size by precision machining; the truncated cone is subjected to a reduction process at 3000 min, 0.5 MPa, and 650 ° C to form a light absorption layer on the glass surface. Then, the upper and lower surfaces of the truncated cone with the light absorption layer formed on the surface are mechanically processed. The processed glass is chemically strengthened at 462 ° C for 30 min to obtain the high-strength cover glass material for space use of this embodiment.

[0079] It was tested that the spectral transmittance of the light-transmitting effective area of ​​the high-strength cover glass material for space use in this embodiment was 90.39%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment was 0.36%@500 nm, and the bending strength of the glass after chemical strengthening was 200.0 MPa.

[0080] Example 3 The high-strength cover glass blank for space use in this embodiment is composed of the following components in percentage by mass: 52% SiO2, 3% Bi2O3, 1% PbO, 10% Na2O, 6% K2O, 3% B2O3, 12% Al2O3, 5% ZrO2, 6% MgO, 1% CaO, and 1% As2O3.

[0081] Quartz sand, bismuth oxide, yellow lead, sodium carbonate, potassium nitrate, boron oxide, aluminum hydroxide, zirconium oxide, calcium carbonate, magnesium oxide and white arsenic are used as raw materials. After each glass raw material is mixed in proportion, the batch material is melted at a high temperature of 1567°C, clarified with auxiliary stirring, mechanically formed at 1380°C, and annealed at 501°C to obtain a glass blank.

[0082] The glass blank of this embodiment is processed into a truncated cone of a certain size by precision machining; the truncated cone is subjected to a reduction process at 15000 min, 0.3 MPa, and 536 ° C to form a light absorption layer on the glass surface. Then, the upper and lower surfaces of the truncated cone with the light absorption layer formed on the surface are machined. The processed glass is chemically strengthened at 398 ° C for 500 min to obtain the high-strength cover glass material for space use of this embodiment.

[0083] After testing, the spectral transmittance of the light-transmitting effective area of ​​the high-strength cover glass material for space in this embodiment is 90.77%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 0.22%@500 nm, and the bending strength of the glass after chemical strengthening is 216.7 MPa.

[0084] Example 4 The high-strength cover glass blank for space use in this embodiment is composed of the following components in percentage by mass: 60% SiO2, 0.5% PbO, 15.1% Na2O, 5% K2O, 3% B2O3, 10% Al2O3, 3% ZrO2, 2% MgO, 1% CaO, and 0.4% As2O3.

[0085] Quartz sand, yellow lead, sodium carbonate, potassium carbonate, boric oxide, aluminum hydroxide, zirconium oxide, calcium oxide, magnesium oxide and white arsenic are used as raw materials. After each glass raw material is mixed in proportion, the batch material is melted at a high temperature of 1580°C, clarified by auxiliary stirring, mechanically formed at 1412°C, and annealed at 561°C to obtain a glass blank.

[0086] The glass blank of this embodiment is processed into a truncated cone of a certain size by precision machining; the truncated cone is subjected to a reduction process at 7200 min, 0.15 MPa, and 520 ° C to form a light absorption layer on the glass surface. Then, the upper and lower surfaces of the truncated cone with the light absorption layer formed on the surface are mechanically processed. The processed glass is chemically strengthened at 427 ° C and 420 min to obtain the high-strength cover glass material for space use of this embodiment.

[0087] After testing, the spectral transmittance of the light-transmitting effective area of ​​the high-strength cover glass material for space in this embodiment is 91.28%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 0.30%@500 nm, and the bending strength of the glass after chemical strengthening is 215.2 MPa.

[0088] Example 5 The high-strength cover glass blank for space use in this embodiment is composed of the following components in percentage by mass: 58.1% SiO2, 1.5% Bi2O3, 12% Na2O, 3% K2O, 2% B2O3, 11.9% Al2O3, 1% ZrO2, 4% MgO, 6% CaO, and 0.5% As2O3.

[0089] Quartz sand, bismuth nitrate pentahydrate, sodium nitrate, potassium nitrate, boric oxide, aluminum hydroxide, zirconium oxide, calcium carbonate, basic magnesium carbonate and white arsenic are used as raw materials. The various glass raw materials are mixed in proportion, the batch material is melted at a high temperature of 1582°C, clarified by auxiliary stirring, mechanically formed at 1429°C, and annealed at 524°C to obtain a glass blank.

[0090] The glass blank of this embodiment is processed into a truncated cone of a certain size by precision machining; the truncated cone is subjected to a reduction process of 20,000 min, 0.01 MPa, and 600 ° C to form a light absorption layer on the glass surface. Then, the upper and lower surfaces of the truncated cone with the light absorption layer formed on the surface are machined. The processed glass is chemically strengthened at 480 ° C for 350 min to obtain the high-strength cover glass material for space use of this embodiment.

[0091] According to tests, the spectral transmittance of the light-transmitting effective area of ​​the high-strength cover glass material for space use in this embodiment is 90.63%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 0.24%@500 nm, and the bending strength of the glass after chemical strengthening is 209.6 MPa.

[0092] Example 6 The high-strength cover glass blank for space use in this embodiment is composed of the following components in percentage by mass: 50% SiO2, 1% Bi2O3, 1.5% PbO, 16% Na2O, 4% K2O, 5% B2O3, 15% Al2O3, 1% ZrO2, 3% MgO, 3.3% CaO, and 0.2% As2O3.

[0093] Quartz sand, bismuth oxide, red lead, sodium carbonate, potassium nitrate, boron oxide, aluminum oxide, zirconium oxide, calcium carbonate, magnesium oxide and white arsenic are used as raw materials. The various glass raw materials are mixed in proportion, the batch material is melted at a high temperature of 1600°C, clarified with auxiliary stirring, mechanically formed at 1450°C, and annealed at 580°C to obtain a glass blank.

[0094] The glass blank of this embodiment is processed into a truncated cone of a certain size by precision machining; the truncated cone is subjected to a reduction process at 10000 min, 0.02 MPa, and 610 ° C to form a light absorption layer on the glass surface. Then, the upper and lower surfaces of the truncated cone with the light absorption layer formed on the surface are machined. The processed glass is chemically strengthened at 380 ° C and 600 min to obtain the high-strength cover glass material for space use of this embodiment.

[0095] According to tests, the spectral transmittance of the light-transmitting effective area of ​​the high-strength cover glass material for space use in this embodiment is 91.02%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 0.4%@500 nm, and the bending strength of the glass after chemical strengthening is 206.3 MPa.

[0096] Comparative Example 1 The glass material of this comparative example is composed of the following components in percentage by mass: 60% SiO2, 5% Bi2O3, 10% Na2O, 8% K2O, 10% Al2O3, 5% ZrO2, 1% MgO, and 1% CaO.

[0097] The glass material of this comparative example is prepared according to the method of Example 3, using quartz sand, bismuth oxide, sodium nitrate, potassium carbonate, aluminum hydroxide, zirconium oxide, calcium oxide and basic magnesium carbonate as raw materials.

[0098] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 79.15%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 55%@500 nm, and the bending strength of the glass after chemical strengthening is 101.1 MPa.

[0099] Comparative Example 2 The glass material of this comparative example is composed of the following components in percentage by mass: 50% SiO2, 5% Bi2O3, 15% Na2O, 8% K2O, 5% B2O3, 12% Al2O3, 1% ZrO2, 1% MgO, and 3% As2O3.

[0100] The glass material of this comparative example is prepared according to the method of Example 3, with quartz sand, bismuth oxide, sodium nitrate, potassium carbonate, boron oxide, aluminum hydroxide, zirconium oxide, calcium oxide, basic magnesium carbonate and white arsenic as raw materials.

[0101] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 78.55%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 49.52%@500 nm, and the bending strength of the glass after chemical strengthening is 123.2 MPa.

[0102] Comparative Example 3 The glass material of this comparative example is composed of the following components in percentage by mass: 40% SiO2, 15% Na2O, 10% K2O, 2% B2O3, 24% Al2O3, 8% ZrO2, and 1% As2O3.

[0103] The glass material of this comparative example is prepared by the method of Example 3, with quartz sand, sodium nitrate, potassium nitrate, boron oxide, aluminum oxide, zirconium oxide and white arsenic as raw materials.

[0104] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 81.15%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 67.21%@500 nm, and the bending strength of the glass after chemical strengthening is 119.5 MPa.

[0105] Comparative Example 4 The glass material of this comparative example is composed of the following components in percentage by mass: 72% SiO2, 5% Na2O, and 23% MgO.

[0106] The glass material of this comparative example is prepared by the method of Example 3 using quartz sand, sodium nitrate and magnesium oxide as raw materials.

[0107] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 30.55%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 20.33%@500 nm, and the bending strength of the glass after chemical strengthening is 136.8 MPa.

[0108] Comparative Example 5 The glass material of this comparative example is composed of the following components in percentage by mass: 49% SiO2, 1.8% Bi2O3, 17% Na2O, 10% K2O, 1% B2O3, 10% Al2O3, 2.5% ZrO2, 6% MgO, 1.7% CaO, and 1% As2O3.

[0109] The glass material of this comparative example is prepared according to the method of Example 3, with quartz sand, bismuth oxide, sodium carbonate, potassium nitrate, boron oxide, aluminum hydroxide, zirconium oxide, calcium carbonate, magnesium oxide and white arsenic as raw materials.

[0110] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 75.18%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 1.55%@500 nm, and the bending strength of the glass after chemical strengthening is 165.5 MPa.

[0111] Comparative Example 6 The glass material of this comparative example is composed of the following components in percentage by mass: 52% SiO2, 2% Bi2O3, 10% Na2O, 7% K2O, 15% Al2O3, 6% ZrO2, 6% MgO, 1% CaO, and 1% CeO2.

[0112] The glass material of this comparative example is prepared according to the method of Example 3, with quartz sand, bismuth oxide, sodium carbonate, potassium nitrate, aluminum hydroxide, zirconium oxide, calcium carbonate, magnesium oxide and cerium oxide as raw materials.

[0113] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 72.67%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 2.2%@500 nm, and the bending strength of the glass after chemical strengthening is 170.9 MPa.

[0114] Comparative Example 7 The glass material of this comparative example is composed of the following components in percentage by mass: 58% SiO2, 0.5% Bi2O3, 18% Na2O, 3.5% K2O, 3% B2O3, 12% Al2O3, 2% ZrO2, 1% MgO, 1.5% CaO, and 0.5% NaCl.

[0115] The glass material of this comparative example is prepared according to the method of Example 3, with quartz sand, bismuth oxide, sodium carbonate, potassium carbonate, boron oxide, aluminum hydroxide, zirconium oxide, calcium oxide, magnesium oxide and sodium chloride as raw materials.

[0116] According to the test, the spectral transmittance of the light-transmitting effective area of ​​the glass material in this comparative example is 91.33%@500 nm, the transmittance of the light absorption layer obtained after reduction treatment is 1.15%@500 nm, and the bending strength of the glass after chemical strengthening is 195 MPa.

[0117] The compositions and properties of the glass samples of Examples 1 to 6 and Comparative Examples 1 to 7 of the present invention are shown in Table 1 and Table 2, respectively.

[0118] Table 1 Composition of glass samples of Examples 1 to 6 and Comparative Examples 1 to 7

[0119] Table 2 Performance test results of glass samples of Examples 1 to 6 and Comparative Examples 1 to 7

[0120] It can be seen from Table 2 that the high-strength cover glass material for space use in each embodiment has excellent spectral transmittance, and the minimum spectral transmittance in the light-transmitting effective area is ≥90.00% (@500 nm~1500 nm). The glass after chemical reduction treatment has good stray light elimination and crosstalk prevention performance, and the transmittance of the light absorption layer is ≤0.40%@500 nm. It also has chemically strengthened properties. The bending strength of the glass after chemical strengthening is 200 MPa, and the spectral transmittance of the glass before and after chemical strengthening is basically unaffected.

[0121] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. Although the present application is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A glass composition, comprising, by mass percentage: 50~60% SiO2, 0~3% Bi2O3, 0~5% PbO, 10~18% Na2O, 3~8% K2O, 0~5% B2O3, 10~18% Al2O3, 1~5% ZrO2, 1~6% MgO, 1~6% CaO and 0.1~1% As2O3.

2. The glass composition according to claim 1, characterized in that In terms of mass percentage, its composition includes: 50-60% SiO2, 0-3% Bi2O3, 0-5% PbO, 10-16% Na2O, 3-8% K2O, 0.1-5% B2O3, 10-18% Al2O3, 1-5% ZrO2, 1-6% MgO, 1-6% CaO and 0.1-1% As2O3; Preferably, the composition comprises, by mass percentage, 50-60% SiO2, 0-3% Bi2O3, 0-2.9% PbO, 10-16% Na2O, 3-8% K2O, 0-3% B2O3, 10-17.9% Al2O3, 1-5% ZrO2, 1.1-6% MgO, 1-6% CaO and 0.2-1% As2O3; Preferably, the composition comprises, by mass percentage, 52-60% SiO2, 0-3% Bi2O3, 0-1% PbO, 10-15.9% Na2O, 5-7.9% K2O, 2.1-3% B2O3, 10-15% Al2O3, 2.1-5% ZrO2, 2-6% MgO, 1-6% CaO and 0.2-1% As2O3; Preferably, the composition comprises, by mass percentage, 52-60% SiO2, 0-3% Bi2O3, 0.5-3% PbO, 10-15.9% Na2O, 5-7% K2O, 2.1-3% B2O3, 10-12.9% Al2O3, 2.1-5% ZrO2, 2-6% MgO, 1-6% CaO and 0.4-1% As2O3; Preferably, its composition includes, by mass percentage, 52-58% SiO2, 1.6-3% Bi2O3, 0.5-1.4% PbO, 10-11.9% Na2O, 5.1-6% or 6-7.9% K2O, 2.1-3% or 3-4.9% B2O3, 12-12.9% Al2O3, 3.1-5% ZrO2, 5.1-6% MgO, 1-3.2% CaO and 0.6-1% As2O3.

3. The glass composition according to claim 1 or 2, characterized in that: In terms of mass percentage, the content of SiO2 is 52-60%, preferably 52-58.1%, and more preferably 52-54%; Preferably, in terms of mass percentage, the content of Bi2O3 is 0 or 0.5-3%, preferably 1-3%, more preferably 1.5-3%; Preferably, the content of PbO is 0 or 0.5-5%, preferably 0.5-3%, more preferably 0.5-1.5% by mass; Preferably, in terms of mass percentage, the content of Na2O is 10-16%, preferably 10-15.1%, and more preferably 10-13.1%; Preferably, the content of K2O is 3-6% by mass, preferably 4-6%, more preferably 5-6%; Preferably, in terms of mass percentage, the content of B2O3 is 1-5%, preferably 1-3%, more preferably 2-3%; Preferably, in terms of mass percentage, the content of Al2O3 is 10-15%, preferably 10-13%, and more preferably 12-12.9%; Preferably, the content of ZrO2 is 2-5% by mass, more preferably 3-5%; Preferably, in terms of mass percentage, the content of MgO is 2-6%, preferably 3-6%, more preferably 4-6%; Preferably, in terms of mass percentage, the content of CaO is 1-4%, preferably 1-3.3%, and more preferably 1-2%; Preferably, in terms of mass percentage, the content of As2O3 is 0.2-1%, preferably 0.4-1%, and more preferably 0.5-1%.

4. A cover glass blank, which is made of the glass composition according to any one of claims 1 to 3; Preferably, the method for preparing the cover glass blank comprises: After the raw materials are mixed, they are melted at a high temperature of 1540~1600℃, stirred, clarified, and then cooled to 1350~1450℃ for molding. After molding, they are annealed at 450~580℃ to obtain the product.

5. A light-transmitting glass substrate, which is prepared by mechanical processing of the glass blank according to claim 4; Preferably, the mechanical processing includes changing at least one of the physical form, surface quality and appearance of the glass blank; Preferably, the light-transmitting glass substrate is in the shape of a truncated cone; Preferably, the spectral transmittance of the light-transmitting glass substrate to 500nm light is ≥90.00%.

6. A cover glass material, comprising the light-transmitting glass substrate according to claim 5, and a light-absorbing layer disposed on the surface of the light-transmitting glass substrate; Preferably, the spectral transmittance of the light-transmitting glass substrate to 500nm light is ≥90.00%; the spectral transmittance of the light-absorbing layer to 500nm light is ≤0.40%; Preferably, the light absorbing layer is produced on the surface of the light-transmitting glass substrate by reducing the light-transmitting glass substrate; Preferably, the thickness of the light absorbing layer is ≥501 μm; Preferably, the reduction treatment is carried out in a reducing atmosphere, the reduction treatment time is 3000-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 500-650 °C; Preferably, the cover glass material is chemically strengthened glass, and the bending strength of the chemically strengthened cover glass material is ≥200 MPa; wherein, The temperature of the chemical strengthening is 380-480° C., the time is 30-600 min, and the molten salt used for chemical strengthening is selected from one or more of lithium salt, sodium salt and potassium salt.

7. A method for preparing the cover glass material according to claim 6, comprising: obtaining a cover glass blank; Mechanically processing the cover glass blank to obtain a light-transmitting glass substrate; Performing a reduction treatment on the light-transmitting glass substrate so that the surface of the light-transmitting glass substrate forms a light-absorbing layer; Performing secondary mechanical treatment on the light-transmitting glass substrate after reduction treatment to remove part of the light-absorbing layer to expose the light-transmitting area; Chemically strengthening the glass after the secondary mechanical treatment to obtain a chemically strengthened cover glass material; Preferably, the glass composition according to any one of claims 1 to 3 is used to prepare a cover glass blank, wherein the method for obtaining the cover glass blank comprises: mixing the raw materials, melting them at a high temperature of 1540-1600° C., stirring, clarifying, then cooling to 1350-1450° C. for molding, and annealing at 450-580° C. after molding to obtain the cover glass blank; Preferably, the reduction treatment is carried out in a reducing atmosphere, the reduction treatment time is 3000-20000 min, the pressure is 0.01-0.5 MPa, and the temperature is 500-650 °C; Preferably, the temperature of the chemical strengthening is 380-480° C., the time is 30-600 min, and the molten salt used for chemical strengthening is selected from one or more of lithium salts, sodium salts and potassium salts. 8 . A lens, comprising the cover glass material according to claim 6 or the cover glass material prepared by the method according to claim 7 .

9. Application of the glass composition according to any one of claims 1 to 3, the glass cover material according to claim 6, or the lens according to claim 8 in the field of smart technology applications; Preferably, the application fields of the intelligent technology include the field of space detection and the field of intelligent vision.

10. The use according to claim 9, characterized in that: The application is to prepare the lens of the star sensor optical system.